The Immersion Approach in Arabic Language Learning through Interaction with Native Speakers - Beddu Malla, Agussalim; Yani Syahruddin, Suryadi; Nurjannah, Nurjannah; Haeruddin, Haeruddin; Ansar, Ansar (Diwan: Jurnal Bahasa dan Sastra Arab, 2025)
This study aims to analyze the immersion approach through interaction with native speakers a case study on the Arabic Literature Study Program, Faculty of Letters at the Muslim University of Indonesia. The immersion method, which involves intensive interaction with native speakers, is expected to significantly improve students' language skills. This study uses a qualitative method with data obtained through interviews, observations and document analysis, to understand students' experiences and perceptions of learning Arabic through native speakers. The results of the study show that the presence of native speaker lecturers has a positive impact on students' mastery of Arabic, especially in the aspects of pronunciation, and cultural understanding. Students also feel an increase in motivation and confidence in using Arabic. Nonetheless, the study also highlights challenges such as limited resources and heterogeneity in students' language proficiency levels. To overcome these challenges, a comprehensive strategy is needed that involves the development of relevant learning materials, training for native-speaking instructors, and the use of technology. Findings of this study underscore the need for careful planning and adaptive implementation to ensure that the immersion method can provide optimal results in Arabic language learning in higher education This research also provides insights into how other programs can integrate experiences with native speakers, enrich learning content and expand access to Arabic language education for the public. مستخلص تهدف هذه الدراسة إلى تحليل طريقة الانغماس من خلال الناطقين بها في تعلم اللغة العربية ، وهي دراسة حالة عن قسم الأدب العربي بكلية الآداب في جامعة المسلمين الإندونيسية من المتوقع أن تؤدي طريقة الانغماس، التي تتضمن تفاعلا مكثفا مع المتحدثين الأصليين، إلى تحسين المهارات اللغوية للطلاب بشكل كبير. تستخدم هذه الدراسة منهج نوعي مع البيانات التي تم الحصول عليها من خلال المقابلات والملاحظات وتحليل المستندات، لفهم تجارب الطلاب وتصوراتهم حول تعلم اللغة العربية من الناطقين بها . تظهر نتائج الدراسة أن محاضرين من الناطقين بالعربية بها يؤثر تأثيراً إيجابياً في إتقان الطلاب للغة العربية، خاصة في جوانب النطق والفهم الثقافي. يشعر الطلاب أيضا بزيادة الدافع والثقة في استخدام اللغة العربية. ومع ذلك، تسلط الدراسة الضوء أيضا على تحديات مثل الموارد المحدودة وعدم التجانس في مستويات الكفاءة اللغوية لدى الطلاب. للتغلب على هذه التحديات، هناك حاجة إلى استراتيجية شاملة تتضمن تطوير مواد تعليمية ذات صلة، وتدريب المتحدثين الأصليين، واستخدام التكنولوجيا. تؤكد نتائج هذه الدراسة على الحاجة إلى التخطيط الدقيق والتنفيذ التكيفي لضمان أن طريقة الانغماس يمكن أن توفر أفضل النتائج في تعلم اللغة العربية في التعليم العالي. يقدم هذا البحث أيضا رؤى حول كيفية دمج البرامج الدراسية الأخرى للخبرات مع المتحدثين الأصليين لإثراء محتوى التعلم وتوسيع نطاق الوصول إلى تعليم اللغة العربية لعامة الناس. Abstrak Penelitian ini bertujuan untuk menganalisis metode immersion melalui penutur asli dalam belajar bahasa Arab di perguruan tinggi, studi kasus pada Program Studi Sastra Arab, Fakultas Sastra Universitas Muslim Indonesia. Metode immersion, yang melibatkan interaksi intensif dengan penutur asli, diharapkan dapat meningkatkan keterampilan bahasa siswa secara signifikan. Penelitian ini menggunakan metode kualitatif dengan data yang diperoleh melalui wawancara, observasi, dan analisis dokumen untuk memahami pengalaman dan persepsi siswa dalam belajar bahasa Arab melalui penutur asli. Hasil penelitian menunjukkan bahwa kehadiran dosen penutur asli berdampak positif terhadap penguasaan bahasa Arab mahasiswa, terutama dalam aspek pengucapan, intonasi, dan pemahaman budaya. Siswa juga merasakan peningkatan motivasi dan kepercayaan diri dalam menggunakan bahasa Arab. Meskipun demikian, penelitian ini juga menyoroti tantangan seperti sumber daya yang terbatas dan heterogenitas dalam tingkat kemahiran bahasa siswa. Untuk mengatasi tantangan tersebut, diperlukan strategi komprehensif yang melibatkan pengembangan materi pembelajaran yang relevan, pelatihan untuk penutur asli, dan penggunaan teknologi. Temuan penelitian ini menggarisbawahi perlunya perencanaan yang matang dan implementasi adaptif untuk memastikan bahwa metode immersion dapat memberikan hasil yang optimal dalam pembelajaran bahasa Arab di perguruan tinggi. Penelitian ini juga memberikan wawasan tentang bagaimana program studi lain dapat mengintegrasikan pengalaman dengan penutur asli untuk memperkaya konten pembelajaran dan memperluas akses ke pendidikan bahasa Arab untuk masyarakat umum.